2016
DOI: 10.1002/jbm.a.35682
|View full text |Cite
|
Sign up to set email alerts
|

Influence of scaffold morphology on co‐cultures of human endothelial and adipose tissue‐derived stem cells

Abstract: The interior of tissue engineering scaffolds must be vascularizable and allow adequate nutrients perfusion in order to ensure the viability of the cells colonizing them. The promotion of rapid vascularization of scaffolds is critical for thick artificial constructs. In the present study co-cultures of human endothelial and adipose tissue-derived stem cells have been performed in poly(ethyl acrylate) scaffolds with two different pore structures: grid-like (PEA-o) or sponge-like (PEA-s), in combination with a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Arnal-Pastor et al. found that sponge-like scaffolds promoted greater cell organization into tubular-like structures than grid-like scaffolds because the paracrine signaling of stem cells significantly enhanced the activity of endothelial cells [ 60 ]. Qazi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Arnal-Pastor et al. found that sponge-like scaffolds promoted greater cell organization into tubular-like structures than grid-like scaffolds because the paracrine signaling of stem cells significantly enhanced the activity of endothelial cells [ 60 ]. Qazi et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies used higher proportion of hUVECs in co-culture with MSCs, such as 3:1 and 5:1, as MSCs are larger and more proliferative [23,24]. It has been revealed that the ratio of hUVECs to MSCs will diminish with time along the co-culture experiment [24]. In the present study, CCK-8 offered a measurement of the cell viability.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies indicated that a 1:1 ratio of MSCs and hUVECs provided robust and stable vascular networks while enabling bone-like tissue formation [7,22]. However, other studies used higher proportion of hUVECs in co-culture with MSCs, such as 3:1 and 5:1, as MSCs are larger and more proliferative [23,24]. It has been revealed that the ratio of hUVECs to MSCs will diminish with time along the co-culture experiment [24].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro vascularization is another approach, in which endothelial cells (ECs) are used with supporting factors, like angiogenic growth factors or additional cell types and supporting ECM components, to facilitate the de novo generation of vascular-like structures 11 . Accelerated vessel formation and improved maintenance of the formed structures were shown before in co-culture with supporting cells like mesenchymal stem cells (MSCs) 12,13 . Here, MSCs are assumed to function as perivascular cells, supporting angiogenic processes like vessel sprouting, elongation and the stabilization of built vessels 14 .…”
mentioning
confidence: 80%